SP Mean Difference Labeling for Some Families of Graphs - Shalini, P.; Priyadarshini, K. (Research and Applications Towards Mathematics and Computer Science Vol. 9, 2024)
In this chapter, the new concept SP Mean difference labeling has been introduced and a formula for SP mean labeling has been established. A function x is called a SP Mean difference labeling of a graph G with q edges, if the vertices of G to the set \(\{\) 1,2,.....,p\(\}\) such that when each edge \(υ\)v is assigned the label $$x(uv) = {x(u + v) - x(u - v)\over 2},$$then the resulting edges labels are distinct numbers. In this chapter, some families of graphs which admits SP Mean difference labeling are investigted.